OMISSÃO DA LÃ?QUIDA NÃO-LATERAL E OPACIDADE NA AQUISIÇÃO DO PORTUGUÊS BRASILEIRO (Letras & Letras, 2007)
ABSTRACT: This article deals with a case of opacity in language acquisition period. This process is a result of a non-pronunciation of liquid non-lateral consonant /r/ after stop alveolar consonant in a complex onset. These phenomena will be focused on constraint-based theory, that is, Sympathy Theory, an Optimality Theory implementation.